Pengaruh Polyethylene Glycol (PEG) terhadap Hardening Planlet Apel (Malus sp.) Akibat Hiperhidrisitas Secara In Vitro - Ruwiyatul Maslukah; Farida Yulianti; Mochammad Roviq; Mochammad Dawam Maghfoer (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2019)
Hyperhydricity is a change of morphology and physiology that occurs in tissue of plant which found in micropropagation. Failure to overcome this problem has been an effect on the success of acclimatization, because of the planlet produced had stress while acclimatization. The purpose of this study was to determine the effect of PEG to fast hardening of apple plantlet by the effect of hyperhydricity and to get the optimal concentration of PEG. The research was conducted at BALITJESTRO, Batu City, from April-July 2018. The research used a completely randomized design with the treatment of PEG (0, 1, 3, 5 dan 9 g l-1). The variable observation were percentage of surviving planlet, change of morfologhy and leaf colour. The result showed the concentration of PEG 5 g l-1 influenced to the percentage of surviving planlet as the indicator tolerance of planlet on drought stress. Concentration of PEG gave the effect to morfologhy change as the indicator the faster of hardening by the effect of hyperhydricity. The concentration of PEG also influenced to changes of leaf colour from moderate green to dark green which is the indicator of chlorophyll on planlet leaf.